Association of fear assessment in inflammatory rheumatic diseases (FAIR) questionnaire with ankylosing spondylitis quality of life and disease activity in patients with ankylosing spondylitis: Fear assessment questionnaire in ankylosing spondylitis - Keleşoğlu Dinçer, Ayşe Bahar; Sezer, Serdar (Journal of Surgery and Medicine, 2022)
Background/Aim: Fear against disease course, treatment, and limitations in family, work, and social life are commonly seen but mostly overlooked by physicians of patients with chronic inflammatory rheumatic diseases. Ankylosing spondylitis (AS) is a chronic inflammatory disease in young adults characterized by limitations in spinal mobility. The Fear Assessment (FAIR) Questionnaire was designed especially for patients with rheumatoid arthritis and spondyloarthritis to assess the level of fear from the patient’s perspective. Here we evaluate the FAIR score in AS patients and its association with disease activity, AS quality of life (ASQoL), depression, anxiety, and fatigue levels. Methods: This cross-sectional study included 79 patients with AS, and disease activity was assessed by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), AS-Disease Activity Score-C reactive protein, and functional status was assessed by Bath Ankylosing Spondylitis Functional Index (BASFI). Patient global assessment of disease and pain were scored on 0–10 cm visual analog scores. All patients completed FAIR and ASQoL questionnaires. The depression and anxiety were evaluated by Hospital Anxiety and Depression Scale (HADS), and fatigue was assessed by Fatigue Severity Scale (FSS). Results: The mean age of AS patients (62% male) was 41.7 (11.3) years. Most of the patients were on biological disease-modifying anti-rheumatic drugs (bDMARDs). The patients’ median BASDAI, ASDAS-CRP, and BASFI were 5.4 (range, 3.8–7.4), 3.83 (1.4), and 4.0 (range, 2.3–6.2), respectively. The overall FAIR, ASQoL, FSS, HADS-depression, and HADS-anxiety scores were 75 (range, 52–91), 9.6 (5.2), 5.4 (range, 4.1–7), 7.7 (4.4) and 9.6 (5.2), respectively. There were statistically significant correlations between disease activity indices and FAIR, ASQoL, FSS, and HADS scores. The FAIR scores significantly correlated with ASQoL, FSS, and HADS scores. The patients with active disease (BASDAI ≥ 4) had significantly higher levels of FAIR, ASQoL, FSS, and HADS. The best cut-off value for the FAIR score of AS patients with moderate to severe disease activity was 50 (AUC: 0.734, 95% CI [0.599–0.870], P = 0.002), with a sensitivity of 89.8%, specificity of 55%, positive likelihood ratio of 1.99, and Youden index of 0.45. Conclusion: This study shows that AS patients face a high level of fear which is associated with higher disease activity, higher risk of mood disorders, and lower quality of life. Physicians should not only focus on the physical improvement of the patient but also handle the fear of patients against their diseases and their treatment. This holistic approach will improve the dialogue between the physician and the patient, which will result in increased compliance with treatment and will raise the quality of care.